CONTRIBUTION OF DINKAR’S THOUGHT PROCESS IN THE DEVELOPMENT OF INDIAN CULTURE - Kumar, Priyanshu (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Indian culture holds a unique place in the world due to its deep history, diverse traditions and spiritual thinking. Ramdhari Singh ’Dinkar’ gave a new vision to the cultural diversity and values ​​of Indian society in his literature. His major works, such as Sanskriti Ke Char Adhyay and Urvashi, underline the antiquity, richness, and sustainable development of Indian culture. Through his thought process, Dinkar analyzed the religious, social, and historical aspects of Indian society and highlighted the unity prevailing in them. In this research paper, Dinkar’s literature has been studied in the context of his cultural vision. His works attempt to establish a balance between tradition and modernity and show that Indian culture not only preserves ancient values, but also changes with time. His literature focuses on topics such as religious tolerance, social equality, and national consciousness. This study shows that Dinkar’s literature is not only a literary contribution, but it is also a medium for the revival and development of Indian culture. His works made the Indian society aware of its cultural identity and pride, which accelerated the process of cultural and social revival.